• Предмет: Алгебра
  • Автор: Nastya0009
  • Вопрос задан 7 лет назад

решить неравенство 1) x(x+8)(2-3x)>0 уравнение (x^2+4x)(x^2+4x-17)+60=0

Ответы

Ответ дал: mishuris
0

1). \ \x(x+8)(2-3x)>0 \ \x=0 \x+8=0; x=-8 \2-3x=0; -3x=-2; x=frac{2}{3}

 

Расчёт знаков.

а). Пусть x=-9 \ -9*(-9+8)(2-3*(-9))=-9*(-1)*29>0

удовлетворяет

б). Пусть x=-1 \ -1*(-1+8)(2-3*(-1)=-1*7*5<0

не удовлетворяет

в). Пусть x=frac{1}{10} \ frac{1}{10}(frac{1}{10}+8)(2-3*frac{1}{10})=frac{1}{10}*frac{81}{10}frac{17}{10}>0

удовлетворяет

г). Пусть x=1 \ 1(1+8)(2-3*1)=1*9*(-1)<0

не удовлетворяет

 

 

         +               -                  +                    -

++++++++.------------.+++++++++.--------------

                 -8              0                    2

Ответ: x < -8 ; 0 < x < frac{2}{3}

 

2). \ <var>(x^2+4x)(x^2+4x-17)+60=0</var>

заменим переменную: a=(x^2+4x)

получим уравнение:

 

 

a(a-17)+60=0 \a^2-17a+60=0 \ \D=(-17)^2-4*1+60=289-240=49 \x_1=frac{17-7}{2}=5 \ \x_2=frac{17+7}{2}=12

подставляем x^2+4x=5 \ x^2+4x=12 и решаем ещё два уравнения:

а).

 

x^2+4x=5 \x^2+4x-5=0 \ \D=4^2-4*1*(-5)=16+20=36 \x_1=frac{-4-6}{2}=-5 \ \x_2=frac{-4+6}{2}=1

б).

x^2+4x=12 \x^2+4x-12=0 \ \D=-4^2-4*1*(-12)=16+48=64 \x_1=frac{-4-8}{2}=-6 \ \x_2=frac{-4+8}{2}=2

 

Ответ: x=-5 ; x=-6 ; x=1 ; x=2

Похожие вопросы